Separation of structural concerns in physical hypermedia mode - Gordillo, Silvia Ethel; Rossi, Gustavo Héctor; Schwabe, Daniel (2005)
In this paper we propose a modeling and design approach for building physical hypermedia applications, i.e. those mobile applications in which physical and digital objects are related and explored using the hypermedia paradigm. We show that by separating the geographical and domain concerns we gain in modularity, and evolution ease. We first review the state of the art of this kind of software systems, arguing about the need of a systematic modeling approach; we next present a light extension to the OOHDM design approach, incorporating physical objects and "walkable" links; next we generalize our approach and show how to improve concern separation and integration in hypermedia design models. We compare our approach with others in the field of physical and ubiquitous hypermedia and in the more generic software engineering field. Some concluding remarks and further work are finally presented.
Formato de archivo: PDF. -- Este documento es producción intelectual de la Facultad de Informática-UNLP (Colección BIPA / Biblioteca.) -- Disponible también en línea (Cons. 18/06/2014)
Advanced Information Systems Engineering (Lecture Notes in Computer Science), Vol. 3520, pp 446-459
Keywords: OBJECT-ORIENTED HYPERMEDIA DESIGN METHOD - OOHDM; APLICACIONES HIPERMEDIA